Dramarcor: Poéticas de criação do escritor-dramaturgo - SILVA, Andrey Jandison da (2023)
What comes before the writing? This questioning is the genesis of this research, which proposes to investigate the importance of observing everyday life and writing in the processes of dramaturgy creation. To reflect on what contemporary dramaturgy is, some excerpts from theater and philosophy theorists are presented, also to think about the figure of the playwright and the writer, and dissolve limits between these two artistic practices. Next, the figure of the writer-playwright is invoked, a creator who observes life, capturing it through multiple writings, and thereby conceiving his dramaturgies. The objective is to theorize a creative process based on the creation of concepts, the three central ones being epiphany, episodial crystal and fable painting, which refer to the exercises of looking, capturing moments, memories, delusions and dreams that cross the body of the playwright-writer. These captures become the material of his alchemy, his creative process, his sorcery: his multiple writings and languages.